Search and rescue (SAR) operations for the missing Bell 206 Long Ranger helicopter in Sarawak, Malaysia using near real-time airborne hyperspectral imaging system - Jusoff, Kamaruzaman (2008)
Purpose – The aim of this paper is to present the latest advances in real-time airborne hyperspectral sensing applications in identifying and mapping the likely spots to be zeroed in for the SAR operations.